Exercise-induced homeostatic perturbations provoked by singles tennis match play with reference to development of fatigue - Mendez-Villanueva, A.; Fernandez-Fernandez, J.; Bishop, D. (British Journal of Sports Medicine, 2007)
This review addresses metabolic, neural, mechanical and thermal alterations during tennis match play with special focus on associations with fatigue. Several studies have provided a link between fatigue and the impairment of tennis skills proficiency. A tennis player`s ability to maintain skilled on-court performance and/or optimal muscle function during a demanding match can be compromised as a result of several homeostatic perturbations, for example hypoglycaemia, muscle damage and hyperthermia. Accordingly, an important physiological requirement to succeed at competitive level might be the player`s ability to resist fatigue. However, research evidence on this topic is limited and it is unclear to what extent players experience fatigue during high-level tennis match play and what the physiological mechanisms are that are likely to contribute to the deterioration in performance.